The Effect of Trace Ions on the Performance of Reverse Electrodialysis Using Brine/Seawater as Working Pairs - Wang, Zhihao; Li, Jianbo; Wang, Hao; Li, Mengqi; Wang, Lingjie; Kong, Xiangqiang (Frontiers in Energy Research, 2022)
It is promising research to harvest the salinity gradient power (SGP) between concentrated brine emitted from desalination plants and seawater and convert it into electric energy by using reverse electrodialysis (RED). However, trace ions in brine and seawater may affect the performance of the RED stack, and there is little research on the effect. Therefore, this work mainly focuses on the influence of trace ions. The effects of these ions on power density, open-circuit voltage, and internal resistance of the RED stack are analyzed by configuring manual seawater and concentrated brine including K1+, Mg2+, SO42-, Ca2+. Experimental results show that divalent ions (Mg2+, SO42-, Ca2+) can significantly increase the internal resistance of the RED stack and reduce power density. Especially, Mg2+ has the greatest reduction in the output power of the stack. Oppositely, the existence of potassium ions (K1+) in the feed solutions will reduce the internal resistance and improve power output. In addition, increasing the concentration gradient of the feed solution, feed temperature, and flow rate can increase open-circuit voltage, power density of the RED stack, and reduce inner power consumption of the stack. This study can provide references for the recovery of SGP in seawater desalination plants.